Bank survival in Central and Eastern Europe - Kočenda, Evžen 1963-; Iwasaki, Ichirō 1966- (Leibniz Institute for Eastern and Southeastern European Studies, 2019)
We analyze bank survival on large dataset covering 17 CEE markets during the period of 2007–2015 by estimating the Cox proportional hazards model. We group banks across countries and according to their financial soundness. Our results show that progress in banking reforms positively affects bank survival. During global financial crisis, banking reform progress is not linked with improved survival probability, though. On the other hand, during the European sovereign debt crisis and afterwards, banking reform progress contributes to improve survival probability substantially. The economic impact of various determinants is largest for average banks measured by their soundness. Financial indicators predict bank survival rate with intuitively expected impact that is economically less significant in comparison to other factors. Specifically, ownership structure and legal form are the key economically significant factors that exhibit strongest economic effect on bank survival. We further document importance of banks being listed with respect to their survival. We also show that probability of exit increases after number of directors increases beyond a threshold. The results are robust with respect to bank grouping, alternative model specifications, and alternative assumptions on survival distribution.
Keywords: Geschichte 2007-2015; Fortbestand; Bank; Osteuropa